Multimodal poetry as a tool for developing students' critical thinking - Mykytenko, Viktorija (Educological discourse, 2026)
In the modern educational environment, poetry ceases to be an exclusively textual phenomenon and is increasingly integrated into the digital space, where it acquires new forms and functions. Lyrical works today sound in the format of audio poetry, come to life in video interpretations, are combined with graphic elements, and become part of interactive platforms and social networks. Such multimodal poetry opens up new opportunities for teaching Ukrainian literature, as it organically combines emotionality, imagery, and appeal to the reader with modern media tools. The article highlights the concept of multimodal poetry and its educational potential, outlines methodological approaches to the use of digital poetic practices in the school literature course. It analyzes how lyrical texts are transformed in the digital environment through audio, video, visual, and interactive formats, which allows students not only to perceive poetry in a multi-channel manner, but also to critically comprehend its content, form, and context. Examples of multimedia interpretations of works by Ukrainian authors are given, which demonstrate the potential of combining traditional literary heritage with the latest technologies. Practical tools for creating educational tasks, exercises and projects that contribute to the development of critical thinking, the formation of skills in analyzing and interpreting literary texts, as well as media literacy, are separately considered. Particular attention is paid to the problem of forming students' national identity in the process of working with digital poetry, because multimodal interpretations of Ukrainian lyrical works not only expand the horizons of perception, but also actualize cultural codes, symbols and values, important for the modern generation. Thus, multimodal poetry appears as an effective tool for teaching Ukrainian literature, combining traditional and innovative approaches, ensuring the integration of artistic and technological experience and contributing to the development of students' critical thinking in the context of digital culture.